AN ANALYSIS OF FIGURATIVE LANGUAGE IN SELECTED ARIANA GRANDE SONGS - Ni Luh Putu Tarisa Damayanti; I Gusti Ayu Mahatma Agung (IKIP Siliwangi, 2022)
This research aims to identify the types of figurative language used in Ariana Grande’s song lyrics and to describe the contextual meaning. The primary data and secondary data were the two different types of data used in this research. Primary data came from the lyrics of selected Ariana Grande songs, while secondary data came from articles, books, magazines, and journals. The descriptive qualitative method was used in this study. The various types of figurative language found in this study include simile, metaphor, hyperbole, allusion, alliteration, and personification. The study found that the songs mostly use a metaphor. The findings of this research can support learners’ understanding of the meaning of song lyrics that use figurative language. Keywords: Contextual Meaning, Figurative Language, Song Lyrics